The Concept of Structural Da'wah of Palembang City Government in Realizing The Golden City of Darussalam - Muslimin Muslimin (CV. Syntax Corporation Indonesia, 2023)
The structural dakwah is movement of dakwah through inner power of government. The activity of structural dakwah is propagate Islamic value to evolving society, structure, politics, and economic. Thereby, Islam is not only a religion or a name of beliefs or certain forms of worship, it is in fact a way of life, a complete code for the guidance of the individual’s, group’s, and state entire life. This research try to reveal phenomenon on Palembang government structural dakwah through program named “Palembang Emas Darussalam.” Therefore, we can see some results to gain some information about implementing Palembang religious program. This field research using qualitative method focused on analyzing Palembang government structural dakwah. The studies presented in this research also want to know, first, how the implementation Palembang religious program in Palembang. The second is implementing in field of physic or material. Third, how the implementation of Palembang religious program in the field of mental or spiritual. Through this research will be get benefit, first, to get information about structural dakwah of Palembang religious in the field physic material and mental spiritual. This research could be concluded, second, Palembang religious program in the field of physic material among other things: The movement of one thousand one mosque (Gerakan Seribu Satu Masjid), Developing of mosque library (Pengembangan Perpustakaan Masjid), Developing of mosque cooperation (Pengembangan Koperasi Masjid), The movement of loving Islamic teacher (Gerakan Cinta Ustadz Ustzdah), The aids for religion organization (Pembinaan Bantuan Organisasi Keagamaan). Second, Palembang religious program in the field of mental spiritual among other things: Visiting together of Jum’at and Ramadhan moment (Safari Jum’at dan Ramadhan Bersama), improving activity of religion society: To undertake the journey to the ka’bah pilgrimage for a good people and marriage program for the poor people (Peningkatan aktivitas sosial keagamaan: Pemberangkatan Ibadah Haji bagi masyarakat berprestasi dan Nikah massal bagi masyarakat kurang mampu). The Improvement of Islamic Human Resources: Training and development of Badan Amil Zakat, Training and Development of the Candidate of Islamic Propagator, Training and Develompent of management of mosque (Peningkatan Sumber Daya Manusia Islami: Pelatihan Badan Amil Zakat, Pelatihan Calon Da’i, dan Pelatihan Manajemen Masjid), The Improvement of Islamic Art and Culture: Musabaqah Tilawatil al-Qur’an dan Memorizing Islamic Big Days (Peningkatan Seni dan Budaya Islam: Musabaqah Tilawatil al-Qur’an dan Peringatan Hari-hari Besar Islam), Banned place of amusement and Drinking of Alcoholic Beverage distribution (Larangan Tempat Hiburan dan Peradaran Minuman Keras).